Regional developmentalism in West Africa: The case for commodity-based industrialization through regional cooperation in the cocoa-chocolate sector - Jonathan Bashi Rudahindwa; Sophie Van Huellen (Journal of African Trade, 2021)
Regional integration occupies a prominent place in the economic policies of most sub-Saharan African countries. However, despite different waves of initiatives across the African continent, the majority of African regional schemes have not managed to achieve their ambitious goal of promoting sustainable development through trade integration in Africa. In light of this observation and using the West African cocoa-chocolate sector as a case study, we propose the regional developmentalism paradigm as an alternative approach to regionalism in Africa. Regional developmentalism places a particular emphasis on the use of regional and subregional approaches to development. Instead of full-fledged trade liberalization and indiscriminate economic integration, the regional developmentalism paradigm advocates for state-led trade facilitation, regulatory convergence, and capacity-building by adopting policies directed at strategic sectors. We evaluate the potential of the regional developmentalism paradigm to promote economic transformation and commodity-based industrialization against the shortcomings of the current regional integration approach embodied in the institutional framework of the Economic Community of West African States.
Keywords: F02; F13; K33; O13; O24; 330; Cocoa; development; developmental state; ECOWAS; industrialization; regional integration; West Africa